2019 IEEE Global Communications Conference (GLOBECOM) 2019
DOI: 10.1109/globecom38437.2019.9013957
|View full text |Cite
|
Sign up to set email alerts
|

Lossless Compression of Time Series Data with Generalized Deduplication

Abstract: To provide compressed storage for large amounts of time series data, we present a new strategy for data deduplication. Rather than attempting to deduplicate entire data chunks, we employ a generalized approach, where each chunk is split into a part worth deduplicating and a part that must be stored directly. This simple principle enables a greater compression of the often similar, non-identical, chunks of time series data than is the case for classic deduplication, while keeping benefits such as scalability, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In "Lossless Compression of Time Series Data with Generalized Deduplication" [20], the authors presented a new strategy for data deduplication to provide compressed data storage for large amounts of time series data. In their approach, they split each data chunk into a part that must be stored directly and a part worth deduplicating.…”
Section: Introductionmentioning
confidence: 99%
“…In "Lossless Compression of Time Series Data with Generalized Deduplication" [20], the authors presented a new strategy for data deduplication to provide compressed data storage for large amounts of time series data. In their approach, they split each data chunk into a part that must be stored directly and a part worth deduplicating.…”
Section: Introductionmentioning
confidence: 99%
“…Although originally considered for large scale data storage [21,32], GD has been adapted to multi-source data compression protocols [15] and file compression for time-series data [35,37]. This has resulted in lightweight, online compression mechanisms suitable to the Internet of Things (IoT) an file compressors with excellent random access properties.…”
Section: Introductionmentioning
confidence: 99%
“…The method has practical merits, and has been shown to achieve a compression of modelled sensor data in many cases where deduplication is unable to [5]. Another instance is able to achieve a compression comparable to typical lossless compression methods for ECG data, while maintaining benefits from classic deduplication [6]. This paper is a study of the theoretical properties of the technique, and it is shown how generalized deduplication compares to classic deduplication.…”
Section: Introductionmentioning
confidence: 99%